DEVELOPMENT OF STUDENT WORKSHEETWITH GUIDED INQUIRY-BASED TO TRAIN STUDENT’SCRITICAL THINKING SKILL ON ELECTROLYTE AND NONELECTROLYTE SOLUTION MATTER GRADE X - MAYANTI, NUR (Universitas Negeri Surabaya, 2018)
This research aims to develop student worksheet with guided inquiry-based to train student critical thinking skill on electrolyte and non electrolyte solution matters based on validity, practicality and effectiveness. This type of research isresearch development depend on the 4D model, but only to develop stage. The instruments usedisreview sheets, validationsheet, pretest and posttest critical thinking skills of sheet and student questionnaire responses. The data sources from two chemistry lectures and chemistry teacher. The limited trial was conducted on 20 students of X gradeXI MIPA 6 SMAN 1 Manyar then the data can be analyzed using descriptive and quantitative. The results of this reasearch indicate the content validity of 83.80% in the category is very feasible and the construct validity of the percentage of 76.6% in the feasible category. The result of questionnaire from students shows that 87,5% of students give positive response to student worksheet that developed with very feasible criteria. The result of the students' thinking skill test has a range of 73.3% -86.7%, so that the developed student worksheetis categorized as feasible.